Contribution to the study of the hydro-chemical characteristics of the lake ecosystem Dayet Er-Roumi, Morocco - El Ghizi Sara (EDP Sciences, 2021)
The protection of the Freshwater ecosystem is necessary for the ecosystem equilibrium of the aquatic fauna and a healthy diet for the local community. Lake Dayet Er-Roumi (SIBE) is under the pressure of various pollution forms that are, most of the time, a result of human activities. The purpose of this study is to assess the various forms of pollution as well as pollution’s degree and evaluate the quality of the water’s lake and its tributaries through spatio-temporal monitoring of diverse physicochemical parameters during two seasons, autumn (low water period) and spring (high water period), of the year 2019. The variations of physicochemical parameters such as pH, EC, and significant anions, namely: NO3⁻, NO2, NH4+, PO43–, SO4-, and Cl⁻ had been studying at seven stations (five stations at lake level and two stations representing the tributaries). The Results revealed wide variations in the concentrations of different physicochemical parameters between the different samples during the two seasons; the data set indicated high concentrations of chlorides in both seasons, with average nitrates and orthophosphates concentrations during the spring season. The results obtained show a very high electrical conductivity with a pH of the water is very basic, which shows that the lake’s water is immensely loaded with different minerals. These results greatly exceed the standards of fish water quality and also surface water quality.